The Method of Case-Study and its Impact on the Development of Masters’ Skills of Intercultural Communication in Learning Foreign Languages - Liudmyla Vorotniak (Pedagogical Discourse, 2014)
In this article the author analyzes the method of case-study, describes the use of the method in the process of teaching foreign languages. The presented method involves the use of problem-situation analysis, which is based on learning a foreign language with the help of solving specific problems - situations (cases). The main concepts used in the method of case-study are the concepts of «situation» and «analysis.» The main objective of the case is detailed picture of a real-life situation. Thus, the case provides a practical model of the situation. Educational purpose for the practical case is mastersʼ training in certain lexical and grammatical subject. It is revealed that discussion plays an important role in case-study method. An essential feature of the discussion is the level of competence, which depends on the competence of its members. However, a major factor in the discussion is the extent of the teacherʼs control. The method of case-study promotes formation of Mastersʼ analytical, practical, creative, communicative, social skills, broadening of outlook, the skills of intercultural communication.